Differential effects of heart rate reduction by atenolol or ivabradine on peripheral endothelial function in type 2 diabetic patients. Issue 24 (19th October 2012) - Nerla, Roberto; Di Franco, Antonino; Milo, Maria; Pitocco, Dario; Zaccardi, Francesco; Tarzia, Pierpaolo; Sarullo, Filippo Maria; Villano, Angelo; Russo, Giulio; Stazi, Alessandra; Ghirlanda, Giovanni; Lanza, Gaetano Antonio; et al.
Abstract : Objective: To assess whether reduction of heart rate (HR) has beneficial effects on endothelial function in patients with type 2 diabetes mellitus (T2DM). Design: Randomised, double-blind, placebo-controlled study. Setting: University hospital. Patients: 66 T2DM patients without overt cardiovascular disease. Interventions: Patients were randomised to receive for 4 weeks, in addition to their standard therapy, one of the following treatments: atenolol (25 mg twice daily), ivabradine (5 mg twice daily) or placebo (1 tablet twice daily). Main outcome measures: Systemic endothelial function, assessed by flow-mediated dilation (FMD); endothelium-independent vasodilation, assessed by nitrate-mediated dilation (NMD); cardiac autonomic function, assessed by HR variability (HRV). Results: 61 patients completed the study (19, 22 and 20 patients in atenolol, ivabradine and placebo groups, respectively). Compared with baseline, HR was similarly reduced by atenolol (87±13 vs 69±9 bpm) and ivabradine (86±12 to 71±9 bpm), but not by placebo (82±10 vs 81±9 bpm) (p<0.001). FMD improved at follow-up in the atenolol group (4.8±1.7 vs 6.4±1.9%), but not in the ivabradine group (5.2±2.5 vs 4.9±2.2%) and in the placebo group (4.8±1.5 vs 4.7±1.7%) (p<0.01). NMD did not change significantly in any group. HRV parameters did not change in the placebo group; they, instead, consistently increased in the atenolol, whereas a mild increase in SDNNi was only observed in the ivabradine group. A significant correlation was found in the atenolol group between HR and FMD changes (r=−0.48; p=0.04). Conclusions: Despite a comparable reduction in HR, atenolol, but not ivabradine, improved FMD in T2DM patients suggesting that changes in HR are by themselves unlikely to significantly improve endothelial function.